Varicocele indicated scrotoplasty with varicocelectomy: A case report - Hossam S. El-Tholoth (Urology Case Reports, 2021)
A 72 -year- old male patient presented to the clinic complaining of mild dragging scrotal pain and hanging scrotum interfering with his daily activity. Clinical examination revealed grade three left varicocele, enlarged hanging scrotum for more than 15 cm from the scrotal neck. The scrotum was explored and left varicocelectomy was done then scrotoplasty. Fifteen months post-operatively patient has an excellent outcome.